Relating to Rock Art in the Contemporary World : Navigating Symbolism, Meaning, and Significance - Brady, Liam M., 1978-; Taçon, Paul S. C. (Paul Stephen Charles), 1958- (Book collections on Project MUSE., 2016)
"Rock art is considered an archaeological artifact reflecting activities from the past, it is also a phenomenon with present-day meaning and relevance to both indigenous and non-indigenous communities. Challenging traditional ways of thinking about this recognizable form of visual heritage and providing insight into its contemporary significance"--Provided by publisher.